FaceForge: Markerless Non-Rigid Face Multi-Projection Mapping - Siegl, Christian; Lange, Vanessa; Stamminger, Marc; Bauer, Frank; Thies, Justus (IEEE transactions on visualization and computer graphics, 2017)
Recent publications and art performances demonstrate amazing results using projection mapping. To our knowledge, there exists no multi-projection system that can project onto non-rigid target geometries. This constrains the applicability and quality for live performances with multiple spectators. Given the cost and complexity of current systems, we present a low-cost easy-to-use markerless non-rigid face multi-projection system. It is based on a non-rigid, dense face tracker and a real-time multi-projection solver adapted to imprecise tracking, geometry and calibration. Using this novel system we produce compelling results with only consumer-grade hardware.